Teaching cultural studies : methods - matters - models - Linke, Gabriele; Rossow, Holger; Tönnies, Merle (Anglistik & Englischunterricht ;, 2011)
HauptbeschreibungIn previous years, many introductions to cultural studies have been published, but there have been few studies that reflected on and systematised teaching experiences, course design, and teaching and learning techniques in the field. This volume is an attempt to close this gap by recording instructors' experiences and insights and presenting successful models of instruction. The contributions assembled do not only aim to broaden the scope of cultural studies instruction but also to facilitate the design of cultural studies courses. Therefore they contain case studie.